EMPLOYING COGNITIVE ABILITIES IN DEVELOPING STRATEGIC FORESIGHT - Roqaya Kazem Hamza Al-Murshidi (Scholars Digest Publishing, 2023)
The advent of globalization, intense competition, and rapid technological change have led to a significant increase in the instability and complexity of the competitive landscape. Organizations move towards drawing possible future maps consistent with the organization’s capabilities and its ability to innovate the programs and technologies necessary to survive and prosper in the future. The research problem arises through several questions, including whether the cognitive abilities of the working individuals will contribute to achieving strategic foresight in the researched company. The research raises several questions, including what is the relationship between the cognitive abilities of individuals and strategic foresight? What is the effect of cognitive abilities in achieving strategic foresight? How prepared are individuals in the organization under study to bring about change? Does the researched organization possess the capabilities necessary to achieve strategic foresight? The study aims to present the theoretical aspects of the research variables (cognitive abilities and strategic foresight) and to show the extent to which the researched organization adopts the concept of (cognitive abilities and strategic foresight). The importance of the research is highlighted because it deals with basic and important variables to achieve distinction compared to competing organizations in the labor market. It also dealt with an important productive industrial sector (Union Company) and linked two variables: the cognitive abilities of individuals and strategic foresight. And by using the intentional sample, a questionnaire form was distributed to the individuals working in the company. The researcher used statistical programs and methods to process data and information, such as Spss v.28 and Microsoft Excel 2010, to test the research variables.
Keywords: foresight, perception, cognitive abilities, strategic foresight